Impact of intraoperative transesophageal echocardiogram on changes in surgical management among patients undergoing cardiovascular surgery in Thailand - Naruenart Lomarat; Chaiyawat Suppasilp; Chanpitcha Khumchoei Sidfeldt (PLoS ONE, 2026)
Transesophageal echocardiography (TEE) is essential to perioperative cardiac care, providing enhanced cardiac visualization compared to transthoracic echocardiography (TTE), especially in complex cases. While TEE is standard in high-income countries, its utilization in resource-limited settings is not as well-defined. This study aimed to quantify the impact of intraoperative TEE on surgical management at a major tertiary care center in Thailand and to investigate the effects of combining preoperative TTE and TEE on surgical planning. This prospective observational study enrolled 624 adult patients undergoing cardiac surgery from January 2023 to January 2024. All patients received intraoperative TEE, with preoperative assessment conducted via either TTE alone or TTE combined with TEE. The primary outcome was the rate of change in surgical management prompted by new intraoperative TEE findings. Intraoperative TEE findings led to a change in surgical management in 10.58% of all cases (95% CI: 8.28–13.26). The rate of change was higher in patients undergoing preoperative TTE combined with TEE (16.13%) compared to those receiving TTE alone (9.60%); however, after multivariable adjustment, this difference was not statistically significant (adjusted RR 1.18, 95% CI: 0.67–2.09, p = 0.567). The type of surgery was the only independent predictor of management changes, with isolated valve surgery (adjusted RR 2.32, 95% CI: 1.05–5.16) and combined valve with CABG procedures (adjusted RR 3.03, 95% CI: 1.30–7.05) showing the highest likelihood of alteration. Postoperative outcomes, including 30-day mortality and complication rates, were comparable between patients with and without surgical management changes. In this study, intraoperative TEE was associated with changes in surgical decision-making in approximately 10% of cardiac surgeries, suggesting a potential clinical impact, particularly in complex valve-related procedures. The addition of a preoperative TEE, while associated with longer surgical wait times, did not independently associate with the likelihood of intraoperative changes. These findings underscore the crucial role of intraoperative TEE for real-time assessment and support its selective use in high-complexity cases, while also highlighting logistical challenges within resource-limited healthcare systems.